Guru Profesional Sebagai Agen Perubahan Dalam Pendidikan Islam Perspektif Imam Al-Ghazali - Munawir Munawir; Verdina Febriani; Nur Azizah Tohhar (Fakultas Tarbiyah Institut Agama Islam Bani Fattah Jombang, 2025)
The role of teachers in Islamic education is not only limited to teaching knowledge, but also as moral shapers and agents of social change. This article discusses the concept of professional teachers in the perspective of Imam Al-Ghazali and its relevance in answering the challenges of Islamic education today. Imam Al-Ghazali emphasized the importance of moral integrity, sincerity, and intellectual ability in a teacher. In his view, teachers not only convey knowledge, but also instill deep spiritual values to students. This research uses a library research method with a descriptive-analytical approach to Al-Ghazali's works, especially Ihya' Ulumuddin. The results of the study show that professional teachers according to Al-Ghazali must have noble character, sincerity in teaching, and be an example in everyday life. Thus, professional teachers play a strategic role as agents of change in building a generation that is not only intellectually intelligent, but also superior in spirituality and morals. This concept is very relevant to be applied in the context of contemporary Islamic education which is facing moral challenges and value degradation.